A novel atlas of gene expression in human skeletal muscle reveals molecular changes associated with aging. Issue 1 (December 2015) - Su, Jing; Ekman, Carl; Oskolkov, Nikolay; Lahti, Leo; Ström, Kristoffer; Brazma, Alvis; Groop, Leif; Rung, Johan; Hansson, Ola
Abstract Background Although high-throughput studies of gene expression have generated large amounts of data, most of which is freely available in public archives, the use of this valuable resource is limited by computational complications and non-homogenous annotation. To address these issues, we have performed a complete re-annotation of public microarray data from human skeletal muscle biopsies and constructed a muscle expression compendium consisting of nearly 3000 samples. The created muscle compendium is a publicly available resource including all curated annotation. Using this data set, we aimed to elucidate the molecular mechanism of muscle aging and to describe how physical exercise may alleviate negative physiological effects. Results We find 957 genes to be significantly associated with aging (p  < 0.05, FDR = 5 %, n  = 361). Aging was associated with perturbation of many central metabolic pathways like mitochondrial function including reduced expression of genes in the ATP synthase, NADH dehydrogenase, cytochrome C reductase and oxidase complexes, as well as in glucose and pyruvate processing. Among the genes with the strongest association with aging were H3 histone, family 3B (H3F3B, p  = 3.4 × 10−13 ), AHNAK nucleoprotein, desmoyokin (AHNAK, p  = 6.9 × 10−12 ), and histone deacetylase 4 (HDAC4, p  = 4.0 × 10−9 ). We also discover genes previously not linked to muscle aging and metabolism, such as fasciculation and elongation protein zeta 2 (FEZ2, p  = 2.8 × 10−8 ). Out of the 957 genes associated with aging, 21 (p  < 0.001, false discovery rate = 5 %, n  = 116) were also associated with maximal oxygen consumption (VO2MAX ). Strikingly, 20 out of those 21 genes are regulated in opposite direction when comparing increasing age with increasing VO2MAX . Conclusions These results support that mitochondrial dysfunction is a major age-related factor and also highlight the beneficial effects of maintaining a high physical capacity for prevention of age-related sarcopenia.